8 - Advancing Collaboration between African Diaspora and Africa-Based Scholars: Extracts of Interviews with Selected African Diaspora Scholars: by Patrício V. Langa, Patrick Swanzy & Pedro Uetela - Langa, Patrício V.; Swanzy, Patrick; Uetela, Pedro (Journal of Higher Education in Africa, 2022)
A considerable number of African scholars who have migrated to the West have done so due to upheavals in their home country’s economy, poor working conditions, political instability, and a lack of academic freedom and autonomy in their homeland’s higher education systems, many of which are in the process of decolonisation/indigenisation. Drawing on the experiences of four African diaspora scholars – experts in the domains of social sciences and humanities, engineering and education – who visited and collaborated with the Doctoral Programme in Higher Education Studies at the University of the Western Cape’s Institute for Post-School Studies in 2017, this article explores the range of motives for their migration to Western institutions. The article also investigates the importance of the academic diaspora’s contribution to teaching and research in both the West and in Africa, concluding that African diaspora scholars and Africa-based scholars are interdependent when it comes to empowering global science. Patrício V. Langa, University of the Western Cape, South Africa & Eduardo Mondlane University, Maputo, Mozambique. Email: planga@uwc.ac.za; patricio.langa@uem.mz Patrick Swanzy, Post-Doctoral Research Fellow, Institute of Post-School Studies, Faculty of Education, University of the Western Cape, South Africa. Email: ipssdphes@gmail.com Pedro Uetela, Post-Doctoral Fellow, University of the Western Cape and Eduardo Mondlane University. Email: uetelaha@yahoo.com